1995
DOI: 10.2737/pnw-rp-485
|View full text |Cite
|
Sign up to set email alerts
|

Extended rotations and culmination age of coast Douglas-fir: old studies speak to current issues.

Abstract: Curtis, Robert O. 1995. Extended rotations and culmination age of coast Douglas-fir: old studies speak to current issues. Res. Pap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 5 publications
(8 reference statements)
5
24
0
Order By: Relevance
“…2 Sawmill grade logs, whereas the thinned areas yielded 94 percent (95-TH) and 92 percent (80-TH) in these grades. Although no precise records are available, the strategy was to thin from below and attempt to remove mortality and defective trees (Curtis 1995). This practice presumably improved log grade in the residual stand, thereby eliminating the trees that would later yield low-grade logs.…”
Section: Millmentioning
confidence: 99%
See 4 more Smart Citations
“…2 Sawmill grade logs, whereas the thinned areas yielded 94 percent (95-TH) and 92 percent (80-TH) in these grades. Although no precise records are available, the strategy was to thin from below and attempt to remove mortality and defective trees (Curtis 1995). This practice presumably improved log grade in the residual stand, thereby eliminating the trees that would later yield low-grade logs.…”
Section: Millmentioning
confidence: 99%
“…Little information is available about the conditions in these stands at the time they were established, but Curtis (1995) concluded that both Port Blakely installations were probably initially widely spaced. Curtis bases this conclusion on the number of trees present when the stands were first thinned as well as evidence of mortality before thinning.…”
Section: ----------Numbers C ----------mentioning
confidence: 99%
See 3 more Smart Citations